Voice-based Malay command recognition for smart house applications - Masyitah Abu (School of Computer and Communication Engineering, 2019)
The scopes of works are as follows; for smart house application, it only focuses on the command given for fan, light, and television; the command will be recorded in a normal environment room. Normal environment room is a room that only affected by moderate background noise such as the wind sound produced by the fan and electric sound produced by the light when it activates; the speakers choose to undergo this project are of multiple races; the age is ranging between 20 to 30 years old because during this age there are differences between male and female voice. From this information, only 24 speakers are chosen to record 648 samples.